Congenital loss: Loss of an immediate family member prior to or during one's birth. - Shamir, Michal Mahat; Pitcho-Prelorentzos, Shani; Leichtentritt, Ronit D. (Death Studies, 2023)
The loss of a family member is often conceptualized as a disruption in one's life story. However, when a loss occurs prior to, or during, one's birth, the bereaved life stories are not interrupted by the loss, but rather begin with loss. The paper offers a new conceptualization of these losses as "congenital losses" and captures the core aspects of this phenomenon. A qualitative phenomenological analysis of 34 in-depth semi-structured interviews with offspring and siblings whose family members died before/during their birth revealed four main challenges presented by congenital loss: incoherency and fragmentation; storyownership; bond-establishment, and; identity challenges.